Preterm Birth is Associated With Increased Blood Pressure in Young Adult Women. Issue 12 (18th June 2019) - Skudder‐Hill, Loren; Ahlsson, Fredrik; Lundgren, Maria; Cutfield, Wayne S.; Derraik, José G. B.
Abstract : Background: While there is some evidence of elevated blood pressure later in life in preterm survivors, data on adult women are still lacking. Thus, we assessed the associations between preterm birth and blood pressure in young adult women. Methods and Results: We studied 5232 young adult women who volunteered for military service in Sweden between 1990 and 2007. Anthropometric and clinic blood pressure data were collected during the medical examination at the time of conscription. There was a progressive decline in systolic and diastolic blood pressures, as well as in mean arterial pressure, with increasing gestational age. Women born preterm had an adjusted increase in systolic blood pressure of 3.8 mm Hg (95% CI, 2.5–5.1; P <0.0001) and mean arterial pressure of 1.9 mm Hg (95% CI, 0.9–2.8; P =0.0001) compared with young women born at term. Rates of systolic hypertension were also considerably higher in young women born preterm (14.0% versus 8.1%, P <0.0001), as were rates of isolated systolic hypertension. The adjusted relative risk of systolic hypertension in women born preterm was 1.72 (95% CI, 1.26–2.34; P <0.001) that of women born at term or post‐term, but there was no significant difference in the risk of diastolic hypertension (adjusted relative risk, 1.60; 95% CI, 0.49–5.20). Conclusions: Young adult women born preterm display elevated systolic blood pressure and an increased risk of hypertension compared with peers born at term or post‐term. Abstract : See Editorial Jones et al